Zakat Empowerment Model to Increase Income Generating Activities among Mustahik - Sutrisno Sutrisno; Fifi Hakimi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This qualitative study explores a zakat-based empowerment model aimed at enhancing income generating activities (IGA) among mustahik through an integrated framework of capital support, capacity building, and continuous mentoring. Data were collected through in-depth interviews and focus group discussions with mustahik beneficiaries and program managers of productive zakat initiatives in Yogyakarta. The analysis focuses on understanding how productive zakat interventions, entrepreneurial skills development, and institutional support shape mustahik’s business performance and economic independence. The findings reveal that structured training, intensive mentoring, and appropriate business model selection play crucial roles in enabling mustahik to optimize the use of productive zakat and improve their livelihoods. Moreover, financial literacy and ongoing institutional guidance emerge as key determinants of program success, influencing beneficiaries' ability to sustain and grow their microenterprises. This study contributes to the refinement of zakat empowerment frameworks and offers practical recommendations to strengthen the long-term effectiveness and sustainability of zakat-based entrepreneurship programs in poverty alleviation.